Pengelolaan Surat Masuk dan Keluar di MAN 2 Langkat - Aisyah Nurcahyani, Sindi Permata Sari, Pitriani Nasution, Elsya Aminatun Husna, Khikmatu Zahwa, Muam (LPPPI Publishing, 2023)
The management of incoming and outgoing mail in educational institutions, especially Madrasah Aliyah Negeri (MAN) 2 Langkat, plays an important role in running school operations and administration. Although the management of letters is centred in the Administration, there are still some challenges, such as limited storage space, inadequate equipment, and limited number of administrative staff. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation at MAN 2 Langkat. The results showed that the incoming mail management procedure involved several stages, starting from receiving, opening, assessing, recording, to following up on letters. Meanwhile, the management of outgoing mail involves letter writing, content verification, recording, sending, monitoring, archiving, and evaluation. Some of the factors inhibiting mail management at MAN 2 Langkat include limited storage space, inadequate equipment, and limited staff. To overcome these obstacles, it is recommended to hold training for staff, add facilities and equipment, and make routine repairs. In conclusion, letter management at MAN 2 Langkat requires serious attention in improving the efficiency and effectiveness of school administration.